Ecophilosophical Principles for an Ecocentric Environmental Education - David Molina-Motos (MDPI AG, 2019)
As environmental slogans have been permeating the social imaginary and permeating the conceptual and axiological dimensions of the different educational currents, Environmental Education has been prompted to define its own specific nature in contrast to the supposedly more integrative educational movements. In contrast to the historical or meta-theoretical strategies of specification and foundation of environmental education, we propose the establishment of some principles derived from genuinely ecological and ecocentric environmental philosophies; the ecophilosophies. This work reviews—in a conciliatory framework and with a pedagogical interest in mind—the most significant contributions of land ethics, deep ecology, social ecology, ecofeminism and the change of paradigm ecologies. The result is a set of facets, key categories and features that offer an integrated and synoptic view of how Ecocentric Environmental Education (EEE) could be based on ecophilosophical principles. In addition, the contrasting features that define those non-ecocentric perspectives of Environmental Education are proposed, and a deconstructive transition of these in alliance with another reconstructive ecophilosophical feature is suggested as the central intention of the Environmental Education methodology. Finally, the value of the theoretical proposal is defended as a foundation and framework for future pedagogical specifications and methodological developments.